Simulation and experimental study of Pin-Plate DC discharge plasma technique - Kadhim A. Aadim (Iraqi Journal of Physics, 2019)
The present work intends to study of dc glow discharge were generated between pin (cathode) and a plate (anode) in Ar gas is performed using COMSOL were used to study electric field distribution along the axis of the discharge and also the distribution of electron density and electron temperature at constant pressure (P=.0.0mbar) and inter electrode distance (d=4 cm) at different applied voltage for both pin cathode system and plate anode and comparison with experimental results.